The Management and Dissemination of Electronic Navigational Chart Data in the 1990s - Grant, Stephen; Casey, Michael; Evangelatos, Timothy; Hecht, Horst (The International Hydrographic Review, 2015)
The capabilities of Electronic Charts are advancing rapidly and the growth of this new exciting technology will probably accelerate when GPS becomes available within the next few years. A considerable amount of work has been done in developing preliminary specifications and standards for the Electronic Chart and it is clear that accurate, up-to-date, Hydrographic Office chart data will be a key element to the success of these systems in the future. In anticipation of a growing demand for chart data, hydrographic and other agencies would be well advised to devote some attention to the creation of the necessary Electronic Navigational Chart Data Bases and data transfer mechanisms to manage and distribute the Electronic Navigational Chart data and updates. This paper describes some of the work that has been done in these areas recently. An information flow model that was developed by the International Hydrographic Organization Electronic Chart Updating Working Group is presented and the new terms that were needed are defined. Trends in Electronic Chart and related developments are also analyzed to determine what the Electronic Chart might be like in the mid 1990s. The problems of managing and disseminating the Electronic Chart data are also discussed.